Necessity to use Marketing Control Systems - Pehota, Irina (My University, 2014)
Nowadays in the world of marketing relations no enterprise can function properly without a marketing service. Efficient performance of the whole enterprise depends on rationally planned marketing system. In the course of marketing plan fulfillment the current marketing situation changes rapidly forcing enterprises to deviate from aims set forth in the plan and tasks dictated by economic situation. Taking into consideration the existing marketing situation it is necessary to create a marketing control system in order to constantly monitor plans implementation and relevance of the tasks set forth in them.
Keywords: marketing service; marketing; marketing relations; ринкові відносини; маркетинг; маркетингова служба